PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA TEMA LINGKUNGAN SAHABAT KITA KELAS V SD NEGERI 050600 KUALA TAHUN PEMBELAJARAN 2018/2019 - TARIGAN, SISKA RAHAYU BR (Unversitas Katolik Santo Thomas, 2019)
The problem in this study is the student learning outcomes that are still low on the theme of our friend's environment in class V 050600 Kuala State Elementary School. The purpose of this study was to determine the effect of Cooperative Learning Model Type Make A Match on student learning outcomes on the theme of the environment of our friend class V 050600 Kuala State Elementary School Learning Year 2018/2019. This type of research is a quantitative research experimental model with a pretest-posttest Control Group Design research design. The class that became the population in this study was class V-A and class V B, where the total population was 49 students with class V A 24 students, and class V B 25 students. Sampling using simple random sampling technique, and selected class V B as a class given treatment (Treatment). To find out the hypothesis in this study using a different test independent sample t-test in SPSS ver 22. The results showed that the experimental class experienced a learning increase of 101% from the previous pretest. In the experimental class the pretest results were 41.75 and posttest was 84. This is supported by the results of the test of the correlation coefficient can be seen that the correlation coefficient value is 0.863 means r count (0.863)> r table (0.396) then Ha is accepted. Then there is a strong relationship and there is an influence between the type of cooperative learning model Make A Match on the learning outcomes in class V 050600 Kuala State Elementary School. Can also be seen from the results of testing the hypothesis t test where t count> t table is 62,308> 1,713 so that the hypothesis Ha is accepted. This shows the influence of the Make A Match type of cooperative learning model on student learning outcomes on the theme of our friend's environment in class IV 050600 Kuala State Elementary School in the 2018/2019 learning year.